An Appraisal of Regional Development in Eastern Uttar Pradesh - Tiwari, A.K.; Sharma, V. N. (National Geographical Journal of India, 2022)
Regional development refers to the understanding of development in the sense of economic efficiency, inequality, disparities and environmental management in a geographic area. In the past, regional development policy tended to try to achieve these objectives by means of large-scale infrastructure development and by attracting inward investment. Past policies have failed to reduce regional disparities significantly and have not been able to help individual lagging regions to catch up, despite the allocation of significant public funding. The result is under-used economic potential and weakened social cohesion. Eastern Uttar Pradesh is presenting the real pictured of these types of inequality, disparity and poverty since last of 70 years of our independence. It is an economically backward region because of lack of infrastructure and huge population. The development has been assessed with the help of composite index based on twenty indicators (social, economic, health, education and population characteristics etc.). High level disparities have been observed among the districts of the study area. It requires favourable regional policies to remove the backwardness which are differently able, because of Saryupar plain is rich in agricultural activities where as plateau region have some minerals. Spatial variation in regional development has been assessed in this paper.